2001
DOI: 10.1038/sj.jhh.1001226
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and the characteristics of the large arteries in a population study

Abstract: In previous cross-sectional and longitudinal population studies, we found that the slope of systolic pressure on age was steeper in postmenopausal than in premenopausal women. We hypothesised that this observation could be due to a specific effect of menopause on the elasticity of the large arteries. We investigated 315 randomly selected women, aged 30 to 70 years. Based on 5.2 years of follow-up, 166 women were premenopausal and 149 menopausal (44 reaching menopause and 105 postmenopausal). These women were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 39 publications
3
56
2
7
Order By: Relevance
“…4,8 -12,14,31,32 None of these studies determined how increases in arterial stiffness associated with IGM and DM-2 were driven by changes in distension, diameter, and pulse pressure. Additionally, our study is among the first 33 to estimate local pulse pressure by distension waveform calibration, which is more accurate than brachial pulse pressure. 21 Our data are in agreement with the Atherosclerosis Risk In Communities (ARIC) study, which also showed that DM-2 was associated with increased carotid stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 -12,14,31,32 None of these studies determined how increases in arterial stiffness associated with IGM and DM-2 were driven by changes in distension, diameter, and pulse pressure. Additionally, our study is among the first 33 to estimate local pulse pressure by distension waveform calibration, which is more accurate than brachial pulse pressure. 21 Our data are in agreement with the Atherosclerosis Risk In Communities (ARIC) study, which also showed that DM-2 was associated with increased carotid stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that smooth muscle cell hypertrophy underlies increased IMT [16,17]; these structural alterations in smooth muscle then limit vascular dilatory capacity [38] as well. It is likely, then, that any structural benefits of HT underlying lumen diameter and IMT in the older HT women in the current study would translate into preserved dilation to an NO donor (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In women, the enlargement of the internal diameter and the fall in blood velocity are less marked (+3.3% and −10.7%, respectively), causing no modification in peak wall shear stress. Women have stiffer arteries at followup, and it is known that menopause per se may increase arterial stiffness (Staessen et al 2001). Increased arterial stiffness is associated with an increase in the propagation speed of waves, with augmentation of the interaction of the incident and reflected waves (O'Rourke and Hashimoto 2007;Nichols 2005;Sergers 2008).…”
Section: Discussionmentioning
confidence: 99%